Forecasting Efek Pembangunan Dry Port terhadap Pertumbuhan Produk Domestik Regional Bruto: Studi Kasus Sulawesi Selatan - Fadli, Feri; Bayu Pamungkas, Pramudyo (Artinara, 2022)
The economic feasibility of a project is typically measured by the increase in the value of GRDP achieved as a result of the project's generation effect. Especially in the case of transportation infrastructure projects involving a large amount of goods movement or logistics. This is closely related to an increase in a region's economic activity. Ease of access, as well as the availability of adequate transportation and infrastructure, can reduce logistics costs and thus lower the price of goods in circulation. As a result, the effect of dry port development in Sidrap and Jeneponto Regencies, South Sulawesi, on regional economic growth is projected in this article. Forecasting economic growth is based on and refers to the increase in the existing GRDP value as a result of the Dry Port construction. Knowing the impact of development on GRDP allows the project's economic feasibility to be tested and considered in the future. In this case, the Dry Port construction in two sites is feasible based on the GRDP growth.